Search for structure in the B0sπ± invariant mass spectrum. - Cheung, S; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; et al. (American Physical Society, 2016)
The B0sπ± invariant mass distribution is investigated in order to search for possible exotic meson states. The analysis is based on a data sample recorded with the LHCb detector corresponding to 3fb^-1 of pp collision data at √s=7 and 8 TeV. No significant excess is found, and upper limits are set on the production rate of the claimed X(5568) state within the LHCb acceptance. Upper limits are also set as a function of the mass and width of a possible exotic meson decaying to the B0sπ± final state. The same limits also apply to a possible exotic meson decaying through the chain B*0sπ±, B*0s → B0sγ where the photon is excluded from the reconstructed decays.